Chemistry in focus : - Tro, Nivaldo J. (Brooks/Cole Pub., 1998)
What does matter look like at the molecular and atomic level? Why are leaves green? Why do colored fabrics fade upon repeated exposure to sunlight? Why does a pencil leave a mark when dragged across a sheet of paper? All of these basic questions have molecular answers that teach and illustrate chemical principles. Nivaldo Tro introduces each concept with a thought experiment, then develops the chemical principles and concepts involved in a molecular understanding of the experiment. Once students have grasped the basic concepts, they are introduced to consumer applications and environmental problems related to the concepts. Mathematical aspects of chemistry are optional.